Możliwości kreowania markowych produktów turystycznych na Dolnym Śląsku - Gryszel, Piotr (Opportunities for Creating Brand Tourist Products in Lower Silesia Region, 2005)
The article presents opportunities for creating brand tourist products in the region of Lower Silesia. 10 subregions are distinguished, on the area of which brand tourist products can be developed, as well as 6 brand tourist products are pointed to, following the assumptions of National Tourist Product Development Strategy, among which there are: spa tourism, business tourism, active tourism, culture and urban tourism, border area and transit tourism and finally tourism in rural areas. Within the groups of brand products there are also underlined, so called, detailed products. There is also presented a set of activities aiming at the development of already existing products and creating new, attractive brand offers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 158-169